Penerapan Pendekatan Saintifik Terhadap Penggunaan Bahan Ajar Audio Visual Pada Siswa Kelas VIIIa SMP Negeri 1 Tojo Barat Dalam Pembelajaran Bahasa Indonesia - Ulfi, Naswa; Alaydrus, Siti Hadijah; Laki, Ridwan; Purbaya, Tizar; N, Nuraini (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Thisi studyi aimsi toi describei thei application ofi a scientific approach in thei usei ofi audio-visuali teaching materialsi andi its influence on thei learningi outcomesi ofi classi VIIIa studentsi ofi SMP Negerii 1i Tojo Barat in language learning. The scientific approachi wasi choseni becausei iti isi ablei toi encourage students to actively observe, ask questions, try, reason, and communicate learning outcomes. The study used qualitativei methodsi withi datai collectioni techniquesi ini thei formi ofi observation, i interviews, i documentation, i andi pre-testi andi post-test. i Thei resultsi ofi thei studyi showed thati thei usei ofi audio-visual mediai can increase interest ini learning, i understanding of the material, and activei involvementi ofi studentsi ini thei learningi process. i Ini stage I, thei average teacher activity was 68.8, student activity 76, and the highest student learning score was 70 and the lowest 52. After improving the strategy, in stage II there was a significant increase with the average teacher activity reaching 92, student activity 89, and learning scores increasing to 76, the highest and 40, the lowest. The application of a scientific approach based on audio-visual media has proven effective in creating interactive and meaningful learning, andi ini accordancei withi thei characteristicsi ofi students. i The scientific approach combined with audio-visual media has proven effective ini increasingi thei interest, activity, i andi learningi outcomesi ofi classi VIIIa studentsi ofi SMPi Negerii 1i Tojo Barat in learning Indonesian.